Phosphorus fertilizer effects on soil phosphorus pools in acid upland soils - Dobermann, Achim; George, Thomas; Thevs, Niels (Wiley, 2002)
Opinions vary on fertilization strategies in part because of uncertainties in methods assessing P supply across sites. We quantified the fate and extractability of fertilizer P after two to four crops with four to five P levels applied to upland rice (Oryza sativa L.)–soybean [Glycine max (L.) Merr.] rotations in three experiments in Asia. Soil P pools were measured by Mehlich‐1 extractant, a modified Hedley fractionation and by mixed‐bed resin capsules after 1 and 14 d (resin adsorption quantity, RAQ‐P1 and RAQ‐P14). Without P addition, 84% of the total P was in the NaOH‐Po and residual‐P fractions across sites. Phosphorus fertilization increased Mehlich‐1 P, resin‐P, NaOH‐Pi, H2SO4‐P, RAQ‐P1, and RAQ‐P14 across sites, whereas NaOH‐Po and residual‐P were unchanged. The sum of resin‐P and NaOH‐Pi increased from 10% to between 20 and 30% of the total soil P. Mehlich‐1 P and resin P increased similarly across sites and fitted quadratic models: the increase in Mehlich‐1 P (mg kg−1 per kg P ha−1) ranged from 0.050 at low P rates to >0.125 at >400 kg P ha−1 The increases per unit P of RAQ‐P, NaOH‐Pi, and H2SO4‐P varied among sites. Oxalate‐extractable Fe accounted for most of the variation in NaOH‐Pi and RAQ‐P. Changes in soil P pools in tropical upland Oxisols and Ultisols following P addition are likely better reflected by NaOH‐Pi and RAQ‐P than Mehlich‐1 P and resin P. Improvements in soil P tests are needed to better discriminate the changes in P pools from fertilization across soils.